PENGARUH KOMPETENSI, MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI LAPAS KELAS IIB MANOKWARI - Lince Bela; Syahruddin Hattab; Obed Bida (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine the influence of competence, motivation, and work culture on employee performance at Class II B Manokwari Correctional Institution. The independent variables in this study are competence, motivation, and work culture while the bound variable is employee performance. The instrument used in data collection is in the form of a questionnaire that will be given a score based on the Likert scale. The population in this study is all employees working in Class II B Manokwari Correctional Institution as many as 74 employees. The number of samples used in this study was 50 respondents The analysis technique uses statistical analysis by testing regression, correlation, determination and hypothesis testing. The results of the study show that partially motivation has a positive and insignificant influence on employee performance, while competence and work culture have a positive and significant effect on employee performance, Simultaneously competence, motivation and work culture have a significant effect on employee performance.